Penerjemahan Pronomina Persona Bahasa Jepang pada Takarir Bahasa Indonesia Anime Tada Never Falls in Love - Fahri Delfariyadi; Siti Shafa Febriani Aryanto (PRASASTI: Journal of Linguistics, 2023)
Personal pronouns are one of the characteristics that distinguishes each language from others. Personal pronouns are linguistic elements that refer to self-referential words. Personal pronouns in Japanese are classified into three types: first-person pronouns, second-person pronouns, and third-person pronouns. Personal pronouns are increasingly being studied not only in linguistics but also in applied linguistics, such as translation studies. Subtitles are used in audiovisual media translation. This research deals at how Japanese personal pronouns are translated into Indonesian subtitles of Yoshiko Nakamura's anime Tada Never Falls in Love. This study utilized two methods, namely data collection and data analysis. The translational equivalent method has been used in this study. Based on the findings, it is possible to conclude that personal pronouns in both the source and target languages have the same meaning components. There are, however, differences in the "gender" meaning component, with the source language preferring a specific gender and the target language preferring neutrality. Other findings from this study include the notion that subtitles in the target language have an informality tendency in the pronoun equivalent, resulting in the loss of gender-preferred speech of personal pronouns in the source language after translation. Furthermore, word-level equivalence can be gained although some meaning and nuance cannot be displayed in the target language.